Comprehensive Assessment of Greenhouse Gas Emissions From Thai Beef Cattle Production and the Effect of Rice Straw Amendment on the Manure Microbiome - Angthong, Wanna; Mori, Akinori; Kitwetcharoen, Haruthairat; Kaeokliang, Ornvimol; Kamphayae, Sukanya; Suzuki, Tomoyuki; Cai, Yimin; Maeda, Koki (Frontiers in Environmental Science, 2022)
We measured the greenhouse gas (GHG) emissions following beef cattle feeding and evaluated the manure management in a northeast Thailand to obtain the country-specific emission factor (EF) and replace the IPCC default value. We fed four Thai native cattle their typical diet of the region and then used the head-cage and dynamic chamber methods to measure the enteric methane (CH4) and GHG emissions during manure storage, respectively. The effect of amending the cattle manure with rice straw on the manure's GHG emission was evaluated. The manure microbiome was monitored by 16S rRNA gene amplicon sequencing and qPCR assay of the functional genes that are required for the methanogenesis and nitrification/denitrification process. The estimated CH4 conversion factor (Ym: 6.87±0.11) was slightly higher than the IPCC default value. The CH4 emission from the manure accounted for 0.69±0.26% of the gross energy intake (GEI). The addition of rice straw slightly lowered the CH4 emission from the manure, but the manure microbiome analysis results showed that it significantly reduced the relative abundance of methanogens (Methanobacteriales), and the functional estimation of manure microbiome agreed with this inhibition effect. The addition of rice straw also showed potential mitigation of the N2O emission with lowered nitrification activity and lower nitrifier abundance, but the results were not consistent between runs. Together these findings will be useful for the higher-tier approach to GHG emissions from beef cattle production systems in tropical regions.